2008
DOI: 10.1002/nme.2477
|View full text |Cite
|
Sign up to set email alerts
|

A hypersingular time‐domain BEM for 2D dynamic crack analysis in anisotropic solids

Abstract: SUMMARYA hypersingular time-domain boundary element method (BEM) for transient elastodynamic crack analysis in two-dimensional (2D), homogeneous, anisotropic, and linear elastic solids is presented in this paper. Stationary cracks in both infinite and finite anisotropic solids under impact loading are investigated. On the external boundary of the cracked solid the classical displacement boundary integral equations (BIEs) are used, while the hypersingular traction BIEs are applied to the crack-faces. The tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The development of anisotropic BEM shows that Dravinski & Wilson (2001), Dravinski (2003), Daros (2013) and Chiang (2018) concentrated on the different aspects of orthotropy effect. Moreover, Wang et al (1996), Zhang (2002), Wunsche et al (2009), Furukawa et al (2014), and Parvanova et al (2016) demonstrated the wave propagation in the anisotropic medium. Also, Zheng & Dravinski (1998, and Dineva et al (2014) investigated the scattering of seismic waves in an orthotropic half-space.…”
Section: Literature Surveymentioning
confidence: 94%
“…The development of anisotropic BEM shows that Dravinski & Wilson (2001), Dravinski (2003), Daros (2013) and Chiang (2018) concentrated on the different aspects of orthotropy effect. Moreover, Wang et al (1996), Zhang (2002), Wunsche et al (2009), Furukawa et al (2014), and Parvanova et al (2016) demonstrated the wave propagation in the anisotropic medium. Also, Zheng & Dravinski (1998, and Dineva et al (2014) investigated the scattering of seismic waves in an orthotropic half-space.…”
Section: Literature Surveymentioning
confidence: 94%
“…In the calculations, displacements and tractions with components u i and t i are prescribed on the grain and phase boundaries (boundary C b ), while relative displacements Du i and stresses r ia are considered in the shear band layers (faces C s ). The computation procedure is based on two boundary integral equations [21]: the displacement boundary integral equation, which is applied on the boundary C b , and the stress boundary integral equation, which is used on the faces C s .…”
Section: Methodsmentioning
confidence: 99%
“…The inconvenience of this approach is that the BEM formulation will now involve integrals including both strong singularities which require special treatment. Numerous hypersingular approaches have been developed, in particular to anisotropic materials under static [ 90 , 91 , 150 , 282 ] and time-harmonic [ 6 , 93 , 94 , 226 , 232 , 283 , 294 ] loadings. The use of a hypersingular formulation does not limit at all the crack shape, being valid for curved and branched cracks, for example.…”
Section: Discrete Numerical Methodsmentioning
confidence: 99%